Total removal of heavy metal from mixed plating rinse wastewater - Sapari, Nasiman; Idris, Azni; Ab. Hamid, Noor Hisham (Elsevier, 1996)
A mixed plating rinse wastewater containing zinc, hexavalent chromium, trivalent chromium, and cyanide with total dissolved solids of 424 mg/1 was treated by a model consisting of a sand filter and ion exchange columns. A strongly acidic cation resin in hydrogen form and a strongly basic anion resin in hydroxide form were used in the columns as cationic and anionic exchangers, respectively. The cationic and anionic exchangers were regenerated by using 2% H2SO4 and 5% NaOH, respectively. A 100% removal of zinc, total chromium, hexavalent chromium and trivalent chromium was achieved in the studies. Very high removal of total dissolved solids, cyanide and hardness level was achieved at 98.9%, 99.9% and 96.5%, respectively. The conductivity of wastewater was reduced from an average of 358 μs/cm to 5 μs/cm. The case study has shown that treatment systems using cationic and anionic resin were able to treat a mixed plating bath effluent to comply with the standard discharge under the Malaysian Environmental Quality (Sewage and Industrial Effluents) Regulation, 1979.